Interaction of Bioactive Compounds from Mentha arvensis with HER2 Receptors as Anti-Breast Cancer Drugs - Elsi Fauzani; Trisna Kumala Sari; Noor Hana Hanif Abu Bakar (Jurnal Riset Sains dan Kimia Terapan, 2026)
Mentha arvensis is a medicinal plant known to contain bioactive compounds such as flavonoids, terpenoids, and phenolic compounds with potential anticancer activity. This study aims to evaluate the potential of compounds from Mentha arvensis as HER2 inhibitors (PDB ID: 5TDN) using an in silico approach. The methods employed include drug-likeness evaluation based on Lipinski’s Rule and molecular docking simulations using PyRx software, with interaction visualization performed using Discovery Studio. The docking results showed that catechin and diosmetin exhibited the best affinity values, at –8.5 kcal/mol. These findings support the potential of compounds from Mentha arvensis as natural anticancer candidates, particularly for breast cancer therapy, although further experimental validation is still required.